Benefits, challenges, characteristics and instructional approaches in an El Sistema inspired after-school string program developed as a university–school partnership in the United States. (May 2017) - Hopkins, Michael; Provenzano, Anthony M.; Spencer, Michael S.
The purpose of this study was to examine the benefits, challenges, program characteristics and instructional approaches of an El Sistema inspired (ESI) after-school string program developed as a university–school partnership. Case study methodology was used to examine the program. Fifth-grade students received 75 minutes of after-school instruction four days per week. Two graduate students in music performance and the elementary school orchestra/general music teacher were the program's lead teachers. Eight additional university students gave pull-out lessons. The program featured many "distinguishing characteristics" described in the ESI literature. The learning environment included large ensemble, sectional learning, and individual lessons. The repertoire learned was standard for American beginning string classes. Teachers provided rigorous expectations for the students to strive for excellence, a safe and supportive learning environment, flexible teaching, and peer-mentoring opportunities. Benefits included high levels of musical achievement, increased learning opportunities, perceived benefits of discipline, perseverance, positive attitude, and hard work. Instructional challenges included low attendance, curricular balance, and teacher collaboration. The intensity and frequency of instruction were found to be the source of most benefits and challenges reported by the participants.